Developments in Bio-Inspired Nanomaterials for Therapeutic Delivery to Treat Hearing Loss - Rathnam, Christopher; Chueng, Sy-Tsong Dean; Ying, Yu-Lan Mary; Lee, Ki-Bum; Kwan, Kelvin (Frontiers in Cellular Neuroscience, 2019)
Sensorineural hearing loss affects millions of people worldwide and is a growing concern in the aging population. Treatment using aminoglycoside antibiotics for infection and exposure to loud sounds contribute to the degeneration of cochlear hair cells and spiral ganglion neurons. Cell loss impacts cochlear function and causes hearing loss in ~ 15% of adult Americans (~36 million). The number of individuals with hearing loss will likely grow with increasing lifespans. Current prosthesis such as hearing aids and cochlear implants can ameliorate hearing loss. However, hearing aids are ineffective if hair cells or spiral ganglion neurons are severely damaged, and cochlear implants are ineffective without properly functioning spiral ganglion neurons. As such, strategies that alleviate hearing loss by preventing degeneration or promoting cell replacement are urgently needed. Despite showing great promise from in vitro studies, the complexity and delicate nature of the inner ear poses a huge challenge for delivering therapeutics. To mitigate risks and complications associated with surgery, new technologies and methodologies have emerged for efficient delivery of therapeutics. We will focus on biomaterials that allow controlled and local drug delivery into the inner ear. The rapid development of microsurgical techniques in conjunction with novel bio- and nanomaterials for sustained drug delivery appears bright for hearing loss treatment.